1987
DOI: 10.1038/clpt.1987.3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of food on the absorption of enteric-coated aspirin: Correlation with gastric residence time

Abstract: The Heidelberg capsule is an indigestible indicator of gastrointestinal pH, which was used to evaluate the relationship between gastric residence time (GRT) and variability in aspirin absorption from enteric-coated tablets. In a crossover study, eight healthy subjects (four men and four women) received an enteric-coated aspirin (648 mg) together with a Heidelberg capsule while fasting or with food (breakfast, followed 4 hours later by lunch). Salicylic acid and salicyluric acid concentrations in plasma and uri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(34 citation statements)
references
References 1 publication
2
32
0
Order By: Relevance
“…As for intake with food, a recent study employing the Heidelberg capsule and a protein-rich breakfast virtually identical to that used in the present and preceding studies, showed that food intake delayed gastric emptying for at least 3-5 h [22,23]. Therefore, little propranolol or atenolol would reach the duodenum within 3-5 h if the drugs were ingested immediately after such a meal.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…As for intake with food, a recent study employing the Heidelberg capsule and a protein-rich breakfast virtually identical to that used in the present and preceding studies, showed that food intake delayed gastric emptying for at least 3-5 h [22,23]. Therefore, little propranolol or atenolol would reach the duodenum within 3-5 h if the drugs were ingested immediately after such a meal.…”
Section: Discussionmentioning
confidence: 87%
“…Furthermore, it has been shown by use of the Heidelberg capsule that concomitant food intake does not delay and it may even accelerate the gastrointestinal absorption of another weakly basic drug, procainamide (pKa = 9), whereas the absorption of a weak acid, acetylsalicylic acid, is delayed for several hours [22,23]. If sufficiently extensive, food-induced gastric absorption would even increase the rate of hepatic delivery of weakly basic, lipophilic drugs, allowing more drug to escape hepatic extraction, and hence explaining part of the increased bioavailability following intake with a proteinrich breakfast.…”
Section: Discussionmentioning
confidence: 98%
“…Absorption of medications in women may be slower due to reduced gastric acid secretion and gastrointestinal motility [6][7][8][9][10][11]. Therefore, drugs designed for absorption in the duodenum, including enteric-coated formulations, may exhibit diminished or delayed absorption, especially following a meal [10,11].…”
Section: Pharmacokineticsmentioning
confidence: 99%
“…Depending on the pharmaceutical formulation, variable results have been obtained also for acetylsalicylic acid [17,67,85], digoxin [8,41,70,73], theophylline [60,62,68,96,104,106], nifedipine [25], indoprofen [107], and iron preparations [28]. Since it is obvious, that the formulation determines whether and how food influences the systemic availability of an active compound, it is necessary to evaluate the effects of concurrent food intake in each individual preparation.…”
Section: Importance Of the Pharmaceutical Formulationmentioning
confidence: 99%